PECULIARITIES OF FIBER FLAX EVALUATION IN SOIL-MELIORATION CONDITIONS OF DRAINAGE - I. V. Ushchapovskii; L. N. Pavlova; E. M. Korneeva; N. B. Brutch (Труды по прикладной ботанике, генетике и селекции)
A comparative evaluation of flax varieties on drained and usual field showed that during significant rainfalls drainage provides increased yields of seeds and straw, and in their lack suppress seeds development. Varieties genotypes influence on high straw yield accumulation is stronger than that on seed formation under the drained conditions during moderate drought in the later stages of vegetation. Use of drained lands for evaluation of the adaptive potential of flax varieties allows identifying their response to different hydrothermal conditions and selects the most promising genotypes.